The Lost of Gospel in The Church and Evangelism in the World: The Deadly Scream and the Answers - Lumintang, Stevri P.N. Indra (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
This research aims to explore the lost Gospel in worldwide churches, especially the evangelical churches in Indonesia and the loss of evangelism in the world. This research was stimulated by the influence of secularism and pragmatism in the church as a result of the change in worldview from the modern era to being postmodern. Based on content analysis research methods, analyzing specifically the contents of several major literatures, it was found that the Gospel and evangelism had indeed disappeared in many church organizations, including evangelical churches and schools of theology in Indonesia. Because of these churches tend to follow the world's mindset and standards, thus leaving the Gospel as the highest standard, as seen in their world-oriented and worldly-inclined way of life. Many churches are conforming to the world. In fact, the loss of the Gospel in the church and evangelization in the world is the biggest and most serious problem in the world, namely moral, mental and spiritual destruction and eternal destruction. For this reason, reformation of the Gospel and evangelism have become an important and urgent agenda, so that the church returns to its nature as a church, the sole agent of God's gospel in the world and returns to its main function, namely evangelizing the world. That is the only solution to the problems of the church and the world. This research is useful for theologians around the world to provide awareness and awareness for the church to carry out its function as the salt and light of the world through the Gospel and evangelism.